SUPPL. Chondrites, Chondrules, Complimentarity and The Depletion Pattern from Cometary dust: the diversity of primitive refractory grains - D. H. Wooden; H. A. Ishii; M. E. Zolensky (2017)
Comet dust is primitive and shows significant diversity. Our knowledge of the properties of primitive cometary particles has expanded significantly through microscale investigations of cosmic dust samples (anhydrous interplanetary dust particles (IDPs), chondritic porous (CP) IDPs and UltraCarbonaceous Antarctic micrometeorites, Stardust and Rosetta ), as well as through remote sensing ( Spitzer IR spectroscopy). Comet dust are aggregate particles of materials unequilibrated at submicrometre scales. We discuss the properties and processes experienced by primitive matter in comets. Primitive particles exhibit a diverse range of: structure and typology; distribution of constituents; concentration and form of carbonaceous and refractory organic matter; Mg- and Fe-contents of the silicate minerals; sulfides; existence/abundance of type II chondrule fragments; high-temperature calcium–aluminium inclusions and ameboid-olivine aggregates; and rarely occurring Mg-carbonates and magnetite, whose explanation requires aqueous alteration on parent bodies. The properties of refractory materials imply there were disc processes that resulted in different comets having particular selections of primitive materials. The diversity of primitive particles has implications for the diversity of materials in the protoplanetary disc present at the time and in the region where the comets formed.